Profil Kecerdasan Emosi Siswa di SMK Negeri I Bonjol - Nurlia, Rosa; Afrinaldi, Afrinaldi (Lembaga Yasin AlSys, 2023)
This research was conducted based on the phenomenon stated at SMKN I Bonjol there were several students who were less able to control their emotions with indications: anxiety in facing exams, students who were unable to control fear when studying with teachers they didn't like or were angry, and uttered harsh words to his friends, students also like to be alone when they have problems, and students also like to scribble on their desks or notebooks, students also like to use harsh words and high tones. The purpose of this study was to find out how big the level of Emotional Intelligence Profile of Students at SMKN I Bonjol. The research method uses a quantitative descriptive approach. The population in this study were 252 class XI students. The research sample consisted of 38 students who were taken using a random sampling technique. Data was collected using the questionnaire method with the Liker Scale instrument and then processed using data analysis techniques using statistical tests with the help of SPSS 16.0. the technique used in processing this research data is statistical test. In this study to see how big the level of Student Intelligence. is to perform statistical tests. The results of statistical tests that have been carried out through the SPSS application, namely that it can be seen that the overall average value is 3.40 with a percentage of 65.59% and a standard deviation of 157.1, it can be concluded that the profile level of the emotional intelligence of students at SMKN I Bonjol is at a high level.